Impact of Corona Virus Outbreak Towards Teaching and Learning Activities in Indonesia - Zaharah Zaharah; Galia Ildusovna Kirilova; Anissa Windarti (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
AbstractLately, the world community was shocked by the Coronavirus outbreak that originated in the city of Wuhan, China that occurred in November 2019 last year. Coronavirus is very dangerous because until now no cure or vaccine has been found. Coronavirus attacks the human respiratory tract quickly. Transmission of this virus through, airborne and air to fellow humans. Its spread is very fast and cross-continent, WHO determined the spread of this virus over the plague and endemic, most of the countries registered at the UN contracted this virus, including Indonesia. This article aims to explain the impact of the coronavirus on teaching and learning activities, which so far teaching and learning processes are held in schools or classes but with the co-19 pandemics, teaching and learning activity is moved at home by E-Learning using various technological devices, such as smartphones, computers, and notebooks. The impact caused by the coronavirus involves various aspects, such as social, cultural, and worse, economic aspects. This study is carried out through a literature study by looking at the results of surveys and studies of literature, journals, and documents of several prints and electronic media and books relating to teaching and social society, sociology and anthropology. The conclusion of this paper shows the government's step in issuing policies to the public not to do any activities outside the home, all work is carried out from home, including teaching and learning activities.Keywords: Impact, Plague, Virus corona, Teaching, and Learning Activities AbstrackAkhir-akhir ini masyarakat dunia digemparkan oleh terjadinya wabah Coronavirus yang berasal dari kota Wuhan, China yang terjadi di bulan November 2019 tahun lalu. Corona virus ini sangat berbahaya karena sampai saat ini belum ditemukan obat atau vaksin penanggulangannya. Coronavirus menyerang saluran pernapasan manusia dengan cepat. Penularan virus ini melalui, airborne dan udara kepada sesama manusia. Penyebarannya yang sangat cepat dan lintas benua, WHO menetapkan penyebaran virus ini diatas wabah dan endemic, sebahagian besar  negara yang terdaftar di PBB terjangkit virus ini, termasuk juga Indonesia.Artikel ini bertujuan untuk menjelaskan dampak dari virus corona  terhadap kegiatan belajar mengajar, yang selama ini proses belajar mengajar diadakan di sekolah atau  kelas tetapi dengan adanya pendemi covid-19, KBM dipindahkan di rumah secara E-Learning dengan mengunakan berbagai alat technologi, seperti smartphone, komputer dan notebook. Dampak yang disebabkan oleh virus corona ini menyangkut perbagai aspek, seperti aspek sosial, budaya, dan yang lebih parah adalah aspek ekonomi. Kajian ini dilakukan melalui studi pustaka dengan melihat hasil-hasil survei dan studi literatur, journal dan document beberapa media cetak maupun elektronik serta buku yang berhubungan dengan pengajaran dan sosial masyrakat, sosiologi dan antropologi. Kesimpulan dari tulisan ini menunjukkan adanya langkah pemerintah mengeluarkan kebijakan kepada masyarakat untuk tidak beraktivitas apapun diluar rumah, semua pekerjaan dilaksanakan dari rumah, termasuk kegiatan belajar dan mengajar (KBM.Keyword: Dampak, Wabah, Viruscorona, Kegiatan Belajar Mengajar